MEMAHAMI PENGALAMAN PROSES KOMUNIKASI PARASOCIAL BREAKUP PADA PENGGEMAR K-POP DI INDONESIA - Lyrasava Fatikha Shailaloka; Hapsari Dwiningtyas Sulistyani (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The parasocial relationship between K-Pop fans and K-pop idols is a relationship built through long term emotional attachment. Under certain conditions, the relationship can experience a rift that leads to it’s termination, known as parasocial breakup. Parasocial breakup is a process that involves a complex communication experience for the fans who undergo it. Therefore, this study aims to explore the lived experiences of the parasocial breakup communication process among K-pop fans in Indonesia. This study adopts a phenomenological approach, guided by Parasocial Relationship Theory (PSR), Parasocial Breakup Theory (PSBR), and Relationship Dissolution Theory. The informants consisted of seven K-Pop fans in Indonesia who had experienced parasocial breakup. Data collection was conducted through in-depth interviews and analyzed using Interpretative Phenomenological Analysis (IPA). The findings show that the communication processes involved in parasocial breakup are divided into two main themes: internal and external processes. Internal processes involve cognitive dissonance, reflection, and contemplation. While external processes include information seeking and management, seeking support and validation, and symbolizing disengagement from the parasocial relationship. These findings indicate that parasocial br